Agriculture's contribution to national emissions - Richards, Meryl B.; Wollenberg, Eva Karoline; Buglion-Gluck S (2015)
This info note offers an overview of the distribution of agricultural emissions among countries and the relative contribution of agriculture to national emissions. It is based on three data sources: the FAOSTAT database of greenhouse gas emissions from agriculture, United States Environmental Protection Agency (EPA) global emission estimates for 2010 and national reports to the United Nations Framework Convention on Climate Change (UNFCCC).1